Productivity model and reference diagram for short rotation biomass crops of poplar grown in Mediterranean environments. (January 2015) - Oliveira, N.; Sixto, H.; Cañellas, I.; Rodríguez-Soalleiro, R.; Pérez-Cruzado, C.
Abstract: A Reference Diagram (RD) was constructed for first rotations of the Euroamerican poplar 'I-214' grown as short rotation coppice (SRC). Data from 144 plots, established in eleven sites in Mediterranean environments, were used to develop the model. The density at establishment of the plantations ranged between 6666 and 33, 333 stools ha −1, covering the usual densities ranges used in short rotation forestry (SRF). The RD was based on a density-independent mortality model that relates the density of living stools to the average height of dominant shoot and the initial plantation density, and it includes a system of two simultaneously fitted equations relating a) quadratic mean basal diameter of dominant shoots to the average height of dominant shoot and the final density, and b) total above-ground woody dry biomass to quadratic mean basal diameter and final density. The isolines in the RD represented mortality, quadratic mean basal diameter of dominant shoots and total above-ground woody dry biomass at the end of a first rotation of three years. The final yield in terms of biomass ranged from 1 to 85 Mg dm ha −1 . The RD enables rapid and straightforward comparison of different situations, both at planting and at harvesting, and is a useful tool, based on a wide range of empirical data, for management and decision making regarding short rotation poplar crops. Highlights: A reference diagram for poplar short rotation coppice is proposed. Models for mortality, quadratic mean basal diameter and dry biomass were fitted. Mortality, quadratic mean basal diameter and dry biomass isolines are plotted. The diagram can be implemented with bioenergy and ash content information.